STUDENTS' MATHEMATICS PROBLEM-SOLVING VIEWED FROM MATHEMATICS ANXIETY AND GENDER - Latifatul Izzah; Muhammad Faslurrohman; Dian Permatasari (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
Some internal factors influence problem-solving ability. Some internal factors that presumably influence problem-solving are mathematics anxiety and Gender. This study aims to determine problem-solving abilities regarding mathematics anxiety and Gender. It is a quantitative research that involves 66 students of a Junior High School in Yogyakarta. The sampling technique used is a simple random sampling technique. The instruments in this study were a problem-solving ability test and a mathematics anxiety questionnaire. The data analysis technique used is Two Way ANOVA. The results show differences in problem-solving ability regarding the students' mathematics anxiety levels. However, there was no difference in students' mathematical problem-solving abilities between male and female students. On the other hand, there is no difference in students' mathematical problem-solving abilities in terms of the level of mathematics anxiety and Gender.